Integration of Augmented Reality and Voice Recognition in Learning English for Children - Dimas Wahyu Wibowo; Ika Kusumaning Putri; Leni Saputri (Universitas Dian Nuswantoro and IndoCEISS, 2022)
Application development by combining two technologies, namely Augmented Reality and Voice Recognition, can make learning media regarding object recognition at home interact directly with 3D virtual objects. The technology can also help the pronunciation or pronunciation of sentences in English. Natural Language Processing (NLP) is used to understand human language so that machines can understand and process it. This ability supports Voice Recognition to have intelligence and interact like humans. wit.ai is an open-source NLP platform that can support speech-to-text application development. The merging of the two technologies in this development using the wit.ai platform. With the wit.ai platform that is used to understand voice commands and perform tasks as needed for applications regarding object recognition at home, users will be able to interact with objects at home through the given voice commands. In the Black Box testing, each functionality got the results that all the features had functioned properly. User Acceptance Test was also carried out and the average test results were 95.77% and 93.26% on a Likert scale with test results on 13 respondents aged 6-9 years old who have tried the application and 14 respondents as observers when 13 respondents aged 6-9 years tried the application. These results show that the application can be accepted and used as a tool in learning media.